(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This work aimed to investigate the effects of different proportions of cardanol ethyl ester (CEE) with diesel in a single cylinder diesel engine on the performance, emissions and combustion parameters. Results show improved performance for blends up to 50% of CEE (B50) content with increase in NOx emissions compared to neat diesel. B25 blends recorded a maximum brake thermal efficiency of 30.71% against 29.13% for the neat diesel at high load. Addition of 2% of isoamyl nitrate with diesel-CEE blends favour higher proportion of CEE to be employed in diesel engine with reduced emissions.